INVESTIGATING PERFORMANCE OF VERTICAL CARBONIZING KILN FOR BRIQUETTE PRODUCTION - Belay, Lulseged; Gabbiye, Nigus (Zede Journal of Ethiopian Engineers and Architects, 2023)
Carbonization experiments of rice husk were carried in pilot cylindrical fluidized bed carbonizing kiln using nitrogen gas as fluidization medium. Husk was collected from rice miller, Amhara Region Wereta Town, Ethiopia and screened by standard sieves. To initate and supply the necessary heat, controlled amount of air is supplied from compressor. Gate valve and air flow meter was installed for regulating and measuring the amount of air.K-type thermocouples and pyrometer were used to monitor progress of bed and external drum temperature distribution. Kiln performance was investigated via studying the effects of air flow rate, air contact time and particle size. The phycochemical properties of raw material and its char were determined by proximate analysis. The results obtained demonistrate that air flow rate, air contact time and particle size have significant effect not on conversion efficiency of kiln and char composition but it affects both carbonization time and temperature distribution of kiln. Generally, char yield varies from 24.87 to 32.49%. Furthermore, lower air flow rate, shorter air contact time and higher particle size is suitable to achiev maximum char yield with 48.63% fixed carbon. Besides, char yield were improved from 18 to 27% to the range of 24.87 to 32.49%.